THE INFLUENCE OF ASSESSMENT, SELF-EFICATION THROUGH STUDENT LEARNING OUTCOMES IN INDONESIAN LANGUAGE - Ijudin (lppm Universitas Negeri Jakarta, 2020)
Abstract This study aimed to learn the results of Indonesian subject which used peer assessment and teacher assessment by the techniques of oral presentations at high school students on the level of different self-efficacy students. The sample was taken were 40 respondents. The data was collected by using an experimental method. Samples were obtained by using stratified random method or multistage random method. The design of treatment which was used was the analysis design treatment by level 2 x 2. The results were found that 1). The test results proved that the average of learning outcomes of Indonesian subject in a group of students who were given ratings by peers had significantly different results compared to the average of learning outcomes of Indonesian subject assessment who were given by the teacher.